Pulsed gas injection: A minimum effort approach for enhanced natural attenuation of chlorobenzene in contaminated groundwater - Balcke, Gerd Ulrich; Paschke, Heidrun; Vogt, Carsten; Schirmer, Mario (My University, 2009)
Chlorobenzene-contaminated groundwater was used to assess pulsed gas sparging as a minimum effort aeration strategy to enhance intrinsic natural attenuation. In contrast to existing biosparging operations, oxygen was supplied at minimum rate by reducing the gas injection frequency to 0.33 day(-1). Field tests in a model aquifer were conducted in a 12 m long reactor, filled with indigenous aquifer material and continuously recharged with polluted groundwater over 3 years. The closed arrangement allowed yield balances, cost accounting as well as the investigation of spatial distributions of parameters which are sensitive to the biodegradation process. Depending on the injection frequency and on the gas chosen for injection (pure oxygen or air) oxygen-deficient conditions prevailed in the aquifer. Despite the limiting availability of dissolved oxygen in the groundwater, chlorobenzene degradation under oxygen-deficient conditions proved to be more effective than under conditions with dissolved oxygen being available in high concentrations. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Groundwater; Oxygen-deficient; Remediation; Oxygenation; Chlorobenzene; WATER TRANSFER; POROUS-MEDIA; OXYGEN; BIODEGRADATION; BIOREMEDIATION; ACCUMULATION; REMEDIATION; DEGRADATION; EXPRESSION; SYSTEM